2003
DOI: 10.1046/j.1474-919x.2003.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use, foraging ecology and diet of Turtle Doves Streptopelia turtur in Britain

Abstract: Since 1968, Turtle Doves Streptopelia turtur in Britain have declined in number by 70% and in breeding range by at least 25%. This study was undertaken during the 1998–2000 breeding seasons at two sites in East Anglia to examine habitat use and foraging ecology. Home ranges of radiotagged Turtle Doves were 0.3–1130 ha in size and contained more woodland than expected from availability. Radiotagged birds undertook foraging trips of up to 10 km. Turtle Doves were recorded feeding primarily at ‘man‐made’ sites (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 12 publications
7
121
0
1
Order By: Relevance
“…The number of chicks fledged per nest was higher in close proximity to cereal crops, and decreased gradually as the distance to the nearest cereal crop increased. This result reinforces the finding that the selection of nest-trees near cereals is beneficial for Turtle-doves (see also Browne & Aebischer, 2003, 2004Dias et al, 2013 andDunn et al, 2016).…”
Section: Determinants Of Reproductive Performancesupporting
confidence: 79%
See 1 more Smart Citation
“…The number of chicks fledged per nest was higher in close proximity to cereal crops, and decreased gradually as the distance to the nearest cereal crop increased. This result reinforces the finding that the selection of nest-trees near cereals is beneficial for Turtle-doves (see also Browne & Aebischer, 2003, 2004Dias et al, 2013 andDunn et al, 2016).…”
Section: Determinants Of Reproductive Performancesupporting
confidence: 79%
“…Potential drivers responsible for the species' decline include nesting habitat degradation , changes in food availability (Browne & Aebischer, 2003) and in wintering grounds, agricultural intensification (Eraud et al, 2009), hunting (Boutin & Lutz, 2007), and variation in ecological conditions throughout the migration route (Browne & Aebischer, 2001, Eraud et al, 2009. Turtle-doves in Europe and Northwest Africa are classified as different subspecies: S. t. turtur and S. t. arenicola respectively (Cramp, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat types reliant on the seeds of arable crops today than in the 1960s, when weed seeds were the staple diet (Browne & Aebischer 2003). Accordingly, two measures of food availability were obtained by classifying habitats as producing either 'natural' foods (weed seeds) based on information supplied by Murton et al (1964), or 'artificial' foods, based on information provided by Browne & Aebischer (2001).…”
Section: Variable Used In Analysismentioning
confidence: 99%
“…This has resulted in its inclusion by the UK government as a Biodiversity Action Plan species (Anon 1995) and it has been the subject of a recent study. Browne & Aebischer (2003) identified that the species has undergone dramatic changes in habitat use and diet over the last 40 years. Browne & Aebischer (2001) showed the importance of hedges and woodland as nesting habitat.…”
mentioning
confidence: 99%
“…switch from spring to autumn sowing of cereals) (Donald et al 2001a(Donald et al , 2002 Corn Bunting productivity is related to pesticide use (Brickle et al 2000) Oilseed rape is the most important farmland nesting habitat for Reed Buntings (D. Gruar et al unpubl. data) and a key food source for Linnets (Moorcroft et al 1997) and Turtle Doves (Browne & Aebischer 2003) Turtle Doves have fewer breeding attempts compared to the 1960s Cirl Buntings require weedy overwinter stubbles near to extensively managed grassland (Evans 1996) Studies of land-uses or land management practices Set-aside can provide an important nesting and foraging habitat for a number of species (Buckingham et al 1999, Henderson et al 2000a, 2000b. In winter, weedy crop stubbles are the most important seed-eating foraging habitats for seed-eating birds (Wilson et al 1996) whilst unimproved pastures are preferred by insectivorous species (Tucker 1992) The structure and management of hedgerows determines their use by breeding birds (Green et al 1994) Bird diversity and the densities of some species can be higher on organic farms compared with conventional farms (Chamberlain et al 1999) Developing and testing of solutions Grey Partridge brood sizes can be nearly doubled by leaving outer 6 m of cereal fields unsprayed by pesticides (Rands 1985) Legal control of predators over a 3-year period increased Grey Partridge breeding density by a factor of 2.6 (Tapper et al 1996) Crop mixtures including kale, quinoa, fat hen and linseed are the most attractive to seed-eating birds (Henderson et al 2001, Boatman & Stoate 2002, Stoate et al 2003 A range of breeding and non-breeding birds responded to management prescriptions on farms taking part in the Arable Stewardship Pilot scheme compared with nearby farms outside the scheme (Bradbury & Allen 2003 Between 1995 and 1998, Cirl Bunting numbers increased by 82% on land under Countryside Stewardship agreement compared with only 2% on nearby non-agreement land (Peach et al 2001) Higher tier wet grassland ESA prescriptions are successful in maintaining or increasing the numbers of breeding Lapwings but lower tier prescriptions are not (Ausden & Hirons 2002) Spring /summer fallows provide Lapwings with nesting habitat throughout the breeding season, increase nest survival and can provide chick-rearing habitat in some instances (Sheldon 2002) Mowing date and method has a hu...…”
Section: (2) Autecological Studiesmentioning
confidence: 99%